1997
DOI: 10.1021/ma961015d
|View full text |Cite
|
Sign up to set email alerts
|

Poly(p-phenylene sulfide) Synthesis:  A Step-Growth Polymerization with Unequal Step Reactivity

Abstract: The anomalous responses of M w to conversion and to comonomer stoichiometry, i.e., deviations from expected classic A−A + B−B step-growth polycondensation behavior, observed in poly(p-phenylene sulfide) synthesis from p-dichlorobenzene and sodium sulfide are shown to be a consequence of unequal rate constants for the growth steps. The polymerization is simulated by a computer model based on the step-growth polymerization concept and includes cyclization and side reactions. Rate constants and activation energie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…Some evidence exists for the ability of an appropriately substituted aromatic thioether to activate halogen substitution by an S N Ar mechanism. For example, in an investigation of poly(phenylene sulfide) synthesis, Fahey and coworkers39, 40 found that bis(4‐chlorophenyl) sulfide could react by an S N Ar mechanism with Na 2 S and was 14 times more reactive toward substitution by Na 2 S in 1‐methyl‐2‐pyrolidinone (NMP) at 200 °C than 1,4‐dichlorobenzene under the same reaction conditions. To investigate the electron‐withdrawing capacity of the thianthrene heterocycle for the activation of fluoro displacement by phenoxides through S N Ar as a route to poly(aryl ether thianthrene)s, we synthesized and characterized the appropriate fluoro‐substituted thianthrene monomer ( 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Some evidence exists for the ability of an appropriately substituted aromatic thioether to activate halogen substitution by an S N Ar mechanism. For example, in an investigation of poly(phenylene sulfide) synthesis, Fahey and coworkers39, 40 found that bis(4‐chlorophenyl) sulfide could react by an S N Ar mechanism with Na 2 S and was 14 times more reactive toward substitution by Na 2 S in 1‐methyl‐2‐pyrolidinone (NMP) at 200 °C than 1,4‐dichlorobenzene under the same reaction conditions. To investigate the electron‐withdrawing capacity of the thianthrene heterocycle for the activation of fluoro displacement by phenoxides through S N Ar as a route to poly(aryl ether thianthrene)s, we synthesized and characterized the appropriate fluoro‐substituted thianthrene monomer ( 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…PPS is produced industrially by the polycondensation reaction of 1,4‐dichlorobenzene with sodium sulfide in N ‐methylpyrrolidinone (NMP) at 200–280 °C under high pressure 2, 37–40. Detailed studies have shown that this polymerization reaction occurs by S N Ar 37, 40.…”
Section: Resultsmentioning
confidence: 99%
“…PPS is produced industrially by the polycondensation reaction of 1,4‐dichlorobenzene with sodium sulfide in N ‐methylpyrrolidinone (NMP) at 200–280 °C under high pressure 2, 37–40. Detailed studies have shown that this polymerization reaction occurs by S N Ar 37, 40. Interestingly, the electron accepting capability of sulfur is apparent in this reaction as the intermediate species bis(4‐chlorophenyl)sulfide is 14 times more reactive toward substitution by sulfide nucleophile than the 1,4‐dichlorobenzene, as shown by model studies 37…”
Section: Resultsmentioning
confidence: 99%
“…The reaction occurs between paradichlorobenzene and the good nucleophile, sodium sulfide. Detailed mechanistic studies have been performed to demonstrate that the reaction occurs by S N Ar whereby the initial activation for para substitution is from the inductive electron withdrawing character of the electronegative chloro group [63,68]. The reaction proceeds quantitatively only at temperatures in excess of 200 8C and only with the strongly nucleophilic sulfide or thiophenoxide.…”
Section: Resultsmentioning
confidence: 99%